Analisis Perkawinan Di Bawah Tangan Menurut Hukum Islam - Anthon Sattu Pabesak; Yoseph Pasolang (LPPM Universitas Ekasakti, 2024)
This study analyzes underhand marriage from the perspective of Islamic law and Law Number 16 of 2019 concerning Marriage. Underhand marriage refers to a marriage that is carried out in accordance with the terms and conditions of Islamic law but does not fulfill the provisions of official registration. This phenomenon has far-reaching legal implications, including the legal status of the couple, the inheritance rights of children, and the validity of the marriage in the state legal system. Through a descriptive qualitative method, this study reveals that religiously, underhand marriages are considered valid, but under state law, their existence is not recognized without official registration. The results also discuss the importance of registration to guarantee the legal rights of all parties involved.